Local and traditional knowledge systems, resistance, and socioenvironmental justice - Natalia Hanazaki (BMC, 2024)
Abstract In this essay, for the debate series of Journal of Ethnobiology and Ethnomedicine, I argue against the oversimplified causal argument that the maintenance of local and traditional knowledge systems is related to less advantaged circumstances. This statement is based on a colonialist perspective of what a less advantageous circumstance is, which is being questioned by several authors. It also ignores the struggles and resistance of traditional knowledge holders and the urgent call for socioenvironmental justice. As an ethnobiologist, I argue that we must face this reality to build science with justice and inclusiveness.